211 A Snapshot Audit of Time to Intervention for Gallstone Pancreatitis During the First Wave of COVID-19. (28th February 2022) - O'Halloran, R.; Coulson, R.; Magee, C.
Abstract: Aim: We evaluated time to definitive treatment of Gallstone Pancreatitis (GSP) against the BSG guidelines during the first wave of COVID-19, comparing it to data of the same time period the previous year. Did the first wave of Covid-19 impact on time to intervention for patients diagnosed with GSP? Method: Data were obtained retrospectively for 40 patients identified via the hospital coding department that presented with GSP between March 2019 - June 2019 and March 2020 – June 2020. Patient demographics, length of stay, time to intervention and re-admission awaiting intervention were recorded. Results: Twenty-three patients were admitted during the non-COVID period. 30% (n = 7) of the non-COVID cohort had definitive management of GSP during index admission or within 2 weeks. Seventeen patients were admitted during the first wave of Covid-19. 64.7% (n = 11) of the COVID-19 cohort had definitive management of GSP during the index admission or within 2 weeks. Conclusions: Prior to COVID-19, we were not meeting guidelines for definitive management on index admission / within 2 weeks. During the first wave of COVID-19, more patients received definitive management of GSP during index admission / within 2 weeks than during the non-COVID period. A higher percentage of patients received surgical management within 2 weeks than in the non-COVID cohort. Those that did not receive management within 2 weeks, waited longer for intervention and had higher rates of re-admission than the non-COVID cohort. Despite anticipated future waves of COVID-19, prioritisation of urgent OP services is essential for those diagnosed with GSP to help reduce re-admission rates whilst awaiting intervention.